ChemInform Abstract: Aerobic Oxysulfonylation of Alkynes in Aqueous Media: Highly Selective Access to β‐Keto Sulfones. Issue 41 (7th October 2014) - Singh, Atul K.; Chawla, Ruchi; Yadav, Lal Dhar S.
Abstract This simple oxysulfonylation protocol involves the FeCl3/K2S2O8 catalyzed formation of sulfonyl radicals from sulfinate salts.